2018
DOI: 10.1016/j.jaci.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

ORAI1 mutations abolishing store-operated Ca2+ entry cause anhidrotic ectodermal dysplasia with immunodeficiency

Abstract: ORAI1 null mutations are associated with reduced numbers of invariant natural killer T and Treg cells that likely contribute to the patients' immunodeficiency and autoimmunity. ORAI1-deficient patients have dental enamel defects and anhidrosis, representing a new form of anhidrotic ectodermal dysplasia with immunodeficiency that is distinct from previously reported patients with anhidrotic ectodermal dysplasia with immunodeficiency caused by mutations in the nuclear factor κB signaling pathway (IKBKG and NFKBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 70 publications
2
67
2
1
Order By: Relevance
“…These types are categorized as follows: type I) hypoplastic enamel defined by enamel that has reduced thickness (volume); type II) hypomaturation defined by normal thickness but mottled appearance, enamel that chips away from the crown, and radiolucency of enamel similar to dentine; type III) hypocalcified when the thickness is normal but the enamel is poorly calcified as identified by less radiolucency of enamel relative to dentine and its appearance is orange-yellow [29]; type IV) a combination that includes several phenotypes such as hypomaturation-hypoplasia with taurodontism (enlarged pulp chamber). Mutations in the STIM1 and ORAI1 genes reported to date cause enamel defects similar to AI, primarily AI type III [5, 6, 8]. …”
Section: Enamelmentioning
confidence: 99%
See 4 more Smart Citations
“…These types are categorized as follows: type I) hypoplastic enamel defined by enamel that has reduced thickness (volume); type II) hypomaturation defined by normal thickness but mottled appearance, enamel that chips away from the crown, and radiolucency of enamel similar to dentine; type III) hypocalcified when the thickness is normal but the enamel is poorly calcified as identified by less radiolucency of enamel relative to dentine and its appearance is orange-yellow [29]; type IV) a combination that includes several phenotypes such as hypomaturation-hypoplasia with taurodontism (enlarged pulp chamber). Mutations in the STIM1 and ORAI1 genes reported to date cause enamel defects similar to AI, primarily AI type III [5, 6, 8]. …”
Section: Enamelmentioning
confidence: 99%
“…A recent study by Lian et al [8] identified three novel autosomal recessive mutations in ORAI1 (p.V181SfsX8, p.L194P and p.G98R). All three mutations resulted in abolished expression of ORAI1 as well as SOCE with impaired T-cell function, reduced numbers of Treg cells though invariant natural killer T (iNKT) cells [8].…”
Section: Enamel Defects In Patients With Loss-of-function Mutation Inmentioning
confidence: 99%
See 3 more Smart Citations